Struktur Modal, Firm Size dan Risiko Bisnis: di Moderasi oleh Profitabilitas - Anisah Anisah; Surayya Surayya; Vitayanti Fattah; Cici Rianty K. Bidin; Faisal Faisal (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study attempts to analyze and explore the impact of capital structure and firm size decisions on business risk mediated by profitability in the context of the pharmaceutical business in Indonesia. In conducting an empirical analysis study, we use panel data from eight companies in the Pharmaceutical Industry sector sourced from the company's annual reports for 2015-2020. The data analysis technique used the Structure Equation Modeling (SEM) method through the Partial Least Square (PLS) approach with WarpPLS 8.0 software. The results of this study found that the capital structure and size of the company have an effect on business risk. Profitability cannot moderate the effect of capital structure on business risk but can moderate the effect of firm size on business risk.